On the Legality of Monopolizing Road Activities Concerning Highways of Regional or Inter-Municipal Significance - V. B. Bashurov (Сибирское юридическое обозрение, 2025)
This article examines the legal norms of the Russian Federation regulating relationships that arise in the course of road activities. The purpose of the study is to analyze the scope and content of road activities, define the limits of public authorities' powers in this area, identify the legal entities directly engaged in such activities—including based on judicial practice—and propose solutions to address violations of antitrust law. The study is grounded in a range of scientific methodologies, including formal legal analysis, structural-functional analysis, comparative method, and the systematic review of academic and regulatory sources. The research draws on the scholarly work of experts in administrative and financial law. The findings suggest that the direct execution of road activities is not legally assigned to public authorities. These bodies merely facilitate the process through administrative and organizational measures, including budgetary funding. The creation of state institutions (including via the reorganization of unitary enterprises) and granting them the right to carry out road works or services results in market monopolization, unjustified state preferences, and violations of public procurement laws. Based on legal analysis and law enforcement practice, the article argues that road activity is an economic function that should be carried out by entities of all forms of ownership and individual entrepreneurs engaged under the law. It is redundant and inappropriate for direct implementation by public authorities. Funding for such activities from the Russian Federation’s budgetary system should be provided through contracts concluded to fulfill public (municipal) needs. Additional financing mechanisms could include budget subsidies for legal entities and entrepreneurs supplying goods, works, and services, or through concession agreements. The study concludes with recommendations for amending federal legislation to ensure consistent legal regulation of the issues discussed.